2021
DOI: 10.1038/s41419-021-03713-9
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoxia-induced miR-210 modulates the inflammatory response and fibrosis upon acute ischemia

Abstract: Hypoxia-induced miR-210 is a crucial component of the tissue response to ischemia, stimulating angiogenesis and improving tissue regeneration. Previous analysis of miR-210 impact on the transcriptome in a mouse model of hindlimb ischemia showed that miR-210 regulated not only vascular regeneration functions, but also inflammation. To investigate this event, doxycycline-inducible miR-210 transgenic mice (Tg-210) and anti-miR-210 LNA-oligonucleotides were used. It was found that global miR-210 expression decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
(59 reference statements)
1
8
0
Order By: Relevance
“…Both SMCs and ECs are involved in vascular remodeling after ischemia in organisms [ 74 ]. The glycocalyx is a general term for the polymorphic glycoproteins that grow in the apical membrane of vascular ECs [ 75 ] and regulate vascular permeability [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both SMCs and ECs are involved in vascular remodeling after ischemia in organisms [ 74 ]. The glycocalyx is a general term for the polymorphic glycoproteins that grow in the apical membrane of vascular ECs [ 75 ] and regulate vascular permeability [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Germana Zaccagnini et al. reported that macrophages with elevated miR-210-3p levels in samples with mismatched miR-210-3p levels in ischemic tissue display dysfunctional angiogenesis, leading to impaired tissue repair ( 51 ). This finding further illustrates the heterogeneity of miR-210-3p function in cells and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that cd320 enhances IL-10-directed B-cell to plasma cell differentiation in germinal centers [ 35 ]. cfa-miR-210 negatively regulates pro-inflammatory cytokines [ 36 ], and miR-210 knockdown in hematopoietic lineage cells attenuates symptoms of parasitic diseases and limits pathogen transmission [ 37 ]. In this study, the upregulation of cfa-miR-210 indicated that the immune activity of the organism could be diminished by targeting syk and cd320 , reducing the B-cell response to antigenic stimulation at 96 hpi.…”
Section: Discussionmentioning
confidence: 99%